Islam and Muslims in the New York Times: two versions, two camps - Alazzany, Murad Ali Obaid Abdullah; Wong, Bee Eng (Universiti Putra Malaysia Press, 2014)
This paper discusses the coverage of Islam and Muslims in the New York Times (NYT) in the wake of the 9/11 events and the ensuing two years. The study shows that coverage of Islam and Muslims takes a new trajectory regarding their representation by which the NYT departs from a monolithic representation towards a fragmented perception. It stays away from the previous themes that have been constantly projected about Islam and Muslims in the western media and provides a more diverse picture. As such, it showed Islam to have two versions, moderate and extremist, and portrayed Muslims based on these two versions. A myriad of diverse themes are manifested and projected in relation to the different versions and camps of Islam and Muslims. From another perspective, the NYT utilizes the essentialization strategy to affiliate extremism to all Islamic movements operating in the domain of politics. It lumps all of them together, portraying them as a threat without concern as to whether they seek political means or use violence to achieve their goals. No distinction is made among these movements in regard to whether they are traditional, modern, violent or peaceful. In adopting this strategy, it thus becomes unclear where moderate Islam ends and where extremism or fundamentalism begins. This dichotomy of Islam and Muslims camps and the essentialization of political Islam are revealed in the light of a multi-disciplinary approach of Critical Discourse Analysis (CDA) in which a textual analysis and a critical linguistic approach are adopted.